The right of access to housing in metropolitan Lima regarding Law 31313, Lay of Sustainable Urban Development and the Draft Regulation on Social Housing - Díaz Rodríguez, Guadalupe (2023)
This article aims to address the issue of access to land and housing deficit in Metropolitan Lima taking into account Law No. 31313, Ley de Desarrollo Urbano Sostenible y la publicación del proyecto de Reglamento de Vivienda de Interés Social, approved by Ministerial Resolution 338-2022-VIVIENDA from November 29, 2022. Moreover, the article seeks to reflect on the social housing policies promoted in recent years to address the qualitative and quantitative housing deficit in Metropolitan Lima.To this end, we first refer briefly to the foundation, recognition and constitutional protection of the right to housing. Then, we address the social and legal context of the demographic increase and informal possession, as well as the background and legislative treatment of this problem in recent years. Finally, we analyse the main proposals and modifications contained in Law No. 31313, the draft Regulation of Social Interest Housing, and the latest developments on the subject, including jurisprudence of the Constitutional Court.